Optimization of BI solution for project management and capacity planning - Constantinov, Daria (2022)
In today’s business environment, effective project management relies on a data-driven decision-making process. As organizations collect a wide range of data, its interpretation and visualization must be conducted effectively. This thesis aims to optimize and improve an existing BI solution, whose main purpose is to support the selected consulting firm in its decision-making process related to project management and employee capacity planning. The best practices in data visualization and data storytelling are used to present the information in the best possible way. The existing BI solution is optimized by automating the ETL process and extended with new visuals using data storytelling. The thesis examines the effect of implementing data storytelling and data visualization best practices on the decision-making process in the selected team. This relationship is studied based on the conducted questionnaire survey. The results of this questionnaire support the original hypothesis that the decision-making process becomes more effective when best practices in data visualization and storytelling are used.